Non-specialist online tool for the assessment of potential damage in residential structures due to severe wind, flood, and earthquake - Bonifacio, Daniel Raymart G.; Pacheco, Benito M.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Philippines is known to be one of those countries frequently affected by natural disasters. This is due to the archipelago's geographic positioning and physical terrain conditions. Residential structures ideally should provide sanctuary to its residents from impending calamities. In this study the vulnerability of structures was calculated using the vulnerability curves and the appropriate hazard maps obtained from the Greater Metro Manila Area - Risk Analysis Project by the UP Diliman Institute of Civil Engineering in 2013. The online tool developed by the researcher, named Hazard Defence, aims to improve on the existing web application named Project Safehouse by Glenn Manalese. Project Safehouse is a non-specialist online tool that calculates the vulnerability index of a structure as a point estimate for severe wind and earthquake, and as a range of values for flood. Using the 95% confidence interval, Hazard Defence outputs a range of values for the potential damage individually for severe wind, flood, and earthquake. In addition, the online tool shares methods on how to lessen the potential damage of a residential structure with respect to the hazard.The non-specialist online tool features include, potential damage ranges for the three hazards, visual aids to guide users in describing their residences, and display of engineering and non-engineering methods to lessen the potential damage of the residence upon the user's discretion. Using the non-parametric sign test, the user assessment survey results indicate that the newly developed online tool named Hazard Defence, is easily understood, instigates awareness on the natural hazards, and gives satisfying results to its users. A future objective of such study as the present one, is to gather, through the online application database, basic socioeconomic data about the application user and to potentially correlate these with the user's attitude in or inclination about the reduction of the estimated potential damage to the structure.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Hazard mitigation -- Philippines; Hazard Defence